PENGARUH KOMPETENSI GURU TERHADAP MOTIVASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PAI KELAS IX DI SMPN 2 MAROS: PENGARUH KOMPETENSI GURU TERHADAP MOTIVASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PAI - Wahyuni, Farida; Mustamin; Wahab, Abdul; Bunyamin, Andi; Syahid, Akhmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to analyze the simultaneous and partial influence of teacher competencies (Pedagogical, Professional, Personality, and Social) on students' learning motivation in Islamic Religious Education (PAI) for Class IX at SMPN 2 Maros. This study employed a quantitative approach with a causal associative research type. The study population was all Class IX students, with a sample of 55 respondents selected using a probability sampling technique. Data were collected through questionnaires converted to a 0-100 scale and analyzed using the multiple linear regression method. The findings indicate that the regression model meets the classical assumptions (normality and no multicollinearity). Simultaneously (F-test), teacher competencies (X1, X2, X3, and X4) significantly influence learning motivation (Y) with a significance value of 0.000 and a coefficient of determination (R^2) of 78.29%. Partially (t-test), all dimensions of teacher competence—Pedagogical (0.0479), Professional (0.0413), Personality (0.0357), and Social (0.0016)—also demonstrate a significant influence on learning motivation as their respective significance values are less than 0.05. The results of effective contribution indicate that Social Competence provides the largest contribution (25.75%) to students' learning motivation. Thus, the quality of teacher competence, particularly social competence, plays a crucial role in enhancing students' learning motivation.